Training-specific effects on metabolic-inflammatory mediators: GLP-1 and Dectin-1 changes following resistance, continuous, or interval exercise in overweight women - Leila Nouri Ain; Valiollah Shahedi; Yaser Kazemzadeh; Sanaz Mirzaian Shanjani; Sajad Arshadi (Journal of Exercise & Organ Cross Talk)
The purpose of this study was to examine the effects of eight weeks of resistance, continuous endurance, and interval endurance training on Dectin-1 and Glucagon-Like Peptide-1 levels in overweight women. A total of 40 women, aged between 25 and 35 years with a body mass index (BMI) ranging from 25 to 30 kg/m², voluntarily participated in the study. Participants were randomly assigned to one of four groups: resistance training (n = 10), continuous endurance training (n = 10), interval endurance training (n = 10), and a non-training control group (n = 10). The intervention consisted of three exercise sessions per week over an eight-week period, following structured and group-specific training protocols. Results indicated that all three exercise modalities—resistance, continuous endurance, and interval training— significantly altered Dectin-1 and GLP-1 levels compared to the control group (p < 0.05). Among the training groups, continuous endurance training elicited the greatest reduction in Dectin-1 levels, followed by interval training and then resistance training. However, post hoc analysis revealed no significant difference between resistance and interval training groups for either biomarker. Similarly, GLP-1 levels increased most prominently in the continuous endurance group, followed by the interval and resistance training groups, again with no significant difference between the latter two. In summary, the findings suggest that all three forms of exercise contributed to favorable changes in Dectin-1 and GLP-1 among overweight women. Nonetheless, the magnitude of these changes appears to be influenced by the type and possibly the intensity of the training stimulus, with continuous endurance training demonstrating the most pronounced effects.